1994
DOI: 10.1093/jnci/86.14.1058
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Plasmacytomas With Silicone Gel Genetically Susceptible Strains of Mice

Abstract: The silicone gels used in mammary implants, which contain a complex mixture of different siloxanes, induced peritoneal plasmacytomas in genetically susceptible mice. Silicone gels provide new chemically defined materials that are effective inducers of plasmacytomas in BALB/cAnPt-A and BALB/cAnPt.DBA/2-Idh1-Pep3 mice. Further studies will be required to determine which of the components of these gels are the active materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…administration of small fragments of a silicone gel. 4 All mice were bred and maintained at our conventional mouse facility (PerImmune, Rockville, MD, USA) under NCI contract N01-BC-21075. Plasmacytomas were diagnosed by finding 10 or more hyperchromatic, atypical plasma cells in cytofuge specimens of ascitic cells that were obtained by abdominal paracentesis and stained with Wright-Giemsa.…”
Section: Induction and Diagnosis Of Plasmacytomasmentioning
confidence: 99%
See 1 more Smart Citation
“…administration of small fragments of a silicone gel. 4 All mice were bred and maintained at our conventional mouse facility (PerImmune, Rockville, MD, USA) under NCI contract N01-BC-21075. Plasmacytomas were diagnosed by finding 10 or more hyperchromatic, atypical plasma cells in cytofuge specimens of ascitic cells that were obtained by abdominal paracentesis and stained with Wright-Giemsa.…”
Section: Induction and Diagnosis Of Plasmacytomasmentioning
confidence: 99%
“…1 In previous work we showed that the T(12;15) translocation comprises a very early and, most likely, initiating oncogenic event in the development of inflammation-induced peritoneal plasmacytomas. 2 Furthermore, the analysis of peritoneal inflammatory granulomas, the tissue site where plasmacytomas develop, 3,4 revealed that numerous T(12;15) + clones were commonly present during tumor latency long before frank malignant growth was observed. [5][6][7] These results suggested that translocated cells residing in inflammatory granulomata constitute a remarkably large and diverse pool of tumor precursor cells from which plasmacytomas could evolve.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma cell tumors arise in BALB/cAnPt mice following 5-12 months of chronic exposure to mineral oil, pristane, or silicone gels (Potter and Boyce, 1962;Potter, 1984;Potter et al, 1994a). These tumors require IL6 (Nordan and Potter, 1986;Hilbert et al, 1995), which activates the Ras/MAP kinase signal transduction pathway for growth (Ogata et al, 1997), and the JAK/STAT3 pathway for antiapoptotic survival factors (Puthier et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmacytomas arise in the peritoneal cavity of BALB/c mice upon induction by a variety of agents including chemical carcinogens such as pristane as well as oncogene containing retroviruses (Potter and Boyce, 1962;Anderson and Potter, 1969;Troppmair et al, 1989;Largaespada et al, 1992;Potter et al, 1994a). A common feature of virtually all pristane induced plasmacytomas is a transcriptionally deregulated c-myc gene (Shen-Ong et al, 1982;Adams et al, 1983;Potter and Wiener, 1992) resulting from a reciprocal chromosomal translocation which, in *90% of cases, involves chromosomes 12 and 15, (t(12;15)).…”
Section: Introductionmentioning
confidence: 99%